Lithogenic potential of pedosphere carbonization: theoretical-methodological, methodical and ecosystem approaches - Hamkalo, Z. G.; Shpakivska, I. M. Shpakivska; Maryskevych, O. G. (AgroChemistry and Soil Science, 2021)
The problem of accumulation and preservation of organic matter (OM) in the pedosphere is one of the main in the world research space. Using the search engine "Google Academy" (Google Scholar) of full texts of scientific publications (articles) on this topic over the past 5 years, showed that the query "carbon sequestration" received – 452,000 sources, and "soil carbon" sequestration " and "soil carbon sequestration potential" – 59,700 and 56,900 sources, respectively, while on request in Ukrainian "carbon sequestration" – 178 and "soil carbon sequestration" – 85. Under these conditions, it is important to inform the Ukrainian reader about the latest achievements of world science on the problem of C-sequestration and C-deposition of various types ecosystems and land use. The presented literature review considers the gradual development of theoretical, methodological and methodical bases for the development of organic matter stabilization models, mainly by a matrix of mineral soils (<20 and <50 μm) using linear least squares regression equations, analysis of limit values and other methodical approaches. Approaches to the assessment of soil carbon capacity (Carbon Protective Capacity), carbon saturation by the mineral matrix (Carbon Saturation, CS), C-saturation of the soil (Saturation Deficit), as well as the functional features of C-sequestration and C-deposition are considered. The existing methods for assessing the stabilization potential of the OM and the reality of the successful implementation of the International Initiative "4 in 1000: Soils for Food Security and Climate", adopted in December 2015, have been critically evaluated. Taking into account the world experience, the need to move to a three-member classification of soil particle size distribution in Ukraine is considered.